(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The subject of this paper being“Androgyny and Virginia Woolf”, an attempt is made to underline the nature ofandrogyny, particularly with reference to this much-misunderstood concept ofman-woman relationship. The radical feminists have denounced this baggage ofandrogyny, saying that it is an inane attempt to escape the pain of feminity onthe part of Virginia Woolf. This criticism mainly comes from Elaine Showalterin her A Literature of Their Own(1978) in which she, as it appears in the very title itself of this book,mocked Woolf. The radical feminist generally feels that Woolf is not much of afeminist because feminism in its third phase, as defined by Showalter herself,pleads for sexual difference.